AB0775 Predictors of osteopenia in a uk population referred for dexa scanning. (23rd January 2014) - Mitchell, K.; Bukhari, M.; Diggle, P.
Abstract : Background: It is acknowledged that the majority of fragility fractures occur in osteopenic individuals 1 . It is not known whether the traditionally defined risk factors for osteoporosis are synonymous with those of osteopenia. Neither is it known whether osteopenia in the spine or the femoral neck are better predictors of future fracture risk. Objectives: To identify and define the predictors of osteopenia in the femoral neck and lumbar spine in an observational cohort of patients referred for DEXA scanning in the North West United Kingdom. Methods: Patients referred for a first DEXA scan at the Rheumatology outpatient department at the Royal Lancaster Infirmary between June 2004 and August 2012 were identified and their data were included in the analysis. Data collected included: age at scan, gender, ethnicity, indication information and densitometry measurements of the femoral neck, total femur and lumbar spine. Two groups of patients were identified at each anatomical site: the 'control' group with normal bone density (T score >-1.0) and an osteopenic group (Tscore < -1 and >-2.5). A student's T test was performed to analyse differences in continuous variables and odds ratios were calculated to assess risk factors of a binary nature using a logistic model. Results: For the femoral neck, data were available on a total of 9262 patients, of which 4241 were in the control group and 5021 in the osteopenic group. At the lumbar spine, data were available on a total of 9310 patients, of which 5573 were controls and 3737 osteopenic. Densitometry data from both sites were available from 8437 patients, therefore the majority of patients feature in both site analyses. Tables 1 and 2 show differences between continuous variables of the two groups at the two sites analysed. Odds ratios for risk of osteopenia with the presence of a classical risk factor for osteoporosis are listed in table 2 . Conclusions: Osteopenic individuals are significantly older, shorter and lighter. Low BMI and previous fracture predict osteopenia but other traditional risk factors for osteoporosis are unreliable predictors of osteopenia in this cohort. Differences exist between predictors of osteopenia at the two sites. Further research is needed. References: Arch Intern Med. 2004 May; 164(10):1108-1112. Disclosure of Interest: None Declared